Inovasi Pelayanan Publik Melalui Sistem Informasi Aspirasi Publik Dan Pengaduan Di Dinas Komunikasi Dan Informatika Kabupaten Sidrap - Zulfikar, Andi M; Mappamiring, Mappamiring; Nasrulhaq, Nasrulhaq (Universitas Muhammadiyah Makassar, 2021)
This study purposed to determine the attributes and aspiration information system innovation strategies public and complaints in managing public complaints at the communication Office and Sidrap regency informatics.The study used qualitative with the type of research descriptive.Data collection techniques were observation,interviews and documentation.The results of the study showed that the innovation in the information system for public aspirations and complaints was very helpful for the publicconvey aspirations and problems encountered relating to services the ease that was accepted by the community with this SIAPP innovation society could make complaints quickly.Simply opened the SIAPP website of the community to make complaints anytime and anywhere.The existence of this SIAPP innovation,the public services was more good. Keywords: innovation,public services,siapp